PID Control Based DC Boost Converter on Wheeled Soccer Robot - Kevin Adrianto Nugraha; Tole Sutikno (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
In this research, Proportional Integral Derivative (PID) controller is applied to the DC-DC Boost Converter system. The system is a power electronics circuit that functions to stabilize the voltage by increasing the value of the output voltage so that it is of a higher value than the input voltage without having to eliminate the relatively large power so that it can overcome the voltage shortage. Control is done by providing a signal or voltage that regulates the ON time and the OFF time of the switch. The voltage value is based on the duty cycle value which is a unit of PWM (Pulse Width Modulation). The input voltage at the boost converter tends to fluctuate and is unstable. On this basis, the output voltage must be controlled by a voltage converter that can be adjusted as desired to match a predetermined setpoint value. By setting the PWM value with the PID method, it is easier to get a constant output voltage value on the boost converter. The results obtained after using a PID control produce a very stable and constant output voltage without any ripple voltage. For the tuning parameter value used to produce a stable output voltage, the proportional value is 5, the integral value is 5, and the derivative value is 3.Pada penelitian ini diterapkan pengendali Proporsional Integral Derivatif (PID) pada sistem DC-DC Boost Converter. Sistem tersebut merupakan suatu rangkaian elektronika daya yang berfungsi untuk menstabilkan tegangan dengan menaikkan nilai tegangan keluaran sehingga bernilai lebih tinggi dari tegangan masukkan tanpa harus menghilangkan daya yang relatif besar sehingga dapat mengatasi kekurangan tegangan. Pengendalian dilakukan dengan memberikan sinyal atau tegangan yang mengatur waktu ON dan waktu OFF switch. Nilai tegangan berdasarkan nilai duty cycle yang merupakan satuan dari PWM (Pulse Width Modulation). Tegangan masukkan pada boost converter cenderung fluktuatif dan tidak stabil. Atas dasar ituÂ  tegangan keluaran harus dikendalikan oleh sebuah konverter tegangan yang dapat diatur sesuai keinginan agar cocok dengan nilai set point yang telah ditetapkan. Dengan mengatur nilai PWM dengan metode PID dapat mempermudah untuk mendapatkan nilai tegangan keluaran yang konstan pada boost converter. Hasil penelitian yang didapatkan setelah menggunakan sebuah kendali PID ini menghasilkan tegangan keluaran yang sangat stabil dan konstan tanpa adanya tegangan ripple. Untuk nilai tuning parameter yang digunakan sehingga menghasilkan tegangan keluaran yang stabil yaitu nilai proporsional adalah 5, nilai integral adalah 5, dan nilai derivatif adalah 3.